High prevalence of fluconazole resistant Candida tropicalis among candiduria samples in China: An ignored matter of concern - Fan, Xin; Tsui, Clement K. M.; Chen, Xi; Wang, Peng; Liu, Zhen-jia; Yang, Chun-xia (Frontiers in Microbiology, 2023)
The rapid rise of azole resistance in Candida tropicalis causing invasive infections has become a public health concern; however, the prevalence of resistant isolates in urine samples was not well studied, because the clinical significance of candiduria was not unambiguous due to possible host colonization. We performed a 12-year laboratory-based surveillance study of C. tropicalis causing either invasive infection or candiduria and studied their susceptibility profiles to common antifungal drugs. A total of 519 unique C. tropicalis strains isolates, 69.9% of which were isolated from urine samples and remaining 30.1% were invasive strains. Overall, 16.5% isolates were confirmed to be resistant to fluconazole, of which 91.9% were cross-resistant voriconazole. Of note, at the beginning of surveillance (2010-2011), the fluconazole resistance rates were low in both candiduria and invasive groups (6.8% and 5.9%, respectively). However, the resistant rate in the candiduria group significantly increased to 29.5% since 2012-2013 (p = 0.001) and stayed high since then, whilst the resistance rate in the invasive group only showed a gradually increasing trends till 2021 (p > 0.05). Sequence analysis of ERG11 gene from fluconazole-resistant strains revealed the prevalence of A395T/W mutation was relatively low (16.7%) in the beginning but reached 87.5%-100% after 2014. Moreover, the A395W heterozygous mutation isolates became predominant (>60% of resistant strains) after 2016, and indeed isolates carrying corresponding amino acid substitution (Y132F) was highly resistant to fluconazole with MIC50 exceeded 256 μg/ml. In conclusion, our study revealed high azole resistant rate in candiduria with its increasing trends observed much earlier than stains causing invasive infections. Given antimicrobial resistance as a critical “One Health” issue, the emergence of antifungal resistance in Candida species that are common commensal colonizers in the human body should be concerned.